2014
DOI: 10.1017/s1461145714000467
|View full text |Cite
|
Sign up to set email alerts
|

Methionine sulfoxide reductase regulates brain catechol-O-methyl transferase activity

Abstract: Catechol-O-methyl transferase (COMT) plays a key role in the degradation of brain dopamine (DA). Specifically, low COMT activity results in higher DA levels in the prefrontal cortex (PFC), thereby reducing the vulnerability for attentional and cognitive deficits in both psychotic and healthy individuals. COMT activity is markedly reduced by a non-synonymous SNP that generates a valine-to-methionine substitution on the residue 108/158, by means of as-yet incompletely understood posttranslational mechanisms. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…In addition, COMT and MSR activities were also correlated in the PFC (but not other brain regions) of Met/ Val carriers. These data support our recent findings on the ability of MSR type A to completely restore the activity of the Met 108 variant in the absence of oxidative conditions [35]. Collectively, the results of these and our previous analyses suggest that the sulphoxidation of the Met 108/158 residue is primarily responsible for the reduction in enzyme activity observed in this variant (Figure ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, COMT and MSR activities were also correlated in the PFC (but not other brain regions) of Met/ Val carriers. These data support our recent findings on the ability of MSR type A to completely restore the activity of the Met 108 variant in the absence of oxidative conditions [35]. Collectively, the results of these and our previous analyses suggest that the sulphoxidation of the Met 108/158 residue is primarily responsible for the reduction in enzyme activity observed in this variant (Figure ).…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that our previous study documented that the enhancement of COMT catalytic activity following addition of MSR‐A was observed in both the Met and Val – containing variants after exposure to stress conditions, suggesting that other Met sulphoxide residues in the primary sequence of COMT may also be targeted by MSR [35]. Given that the degree of sulphoxidation of other Met residues on the Met 108/158 genotype has yet to be determined, this possibility could not be directly verified in the present study; however, the lack of correlations between MSR and COMT in homozygous Val carriers suggests that the oxidation of other Met residues in COMT may need to be accompanied by Met 108/158 variant in order to be influential on the catalytic characteristics of this enzyme in vivo .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in contrast with evidence in vitro , the three COMT rs4680 genotypes were found to be associated with only modest differences in brain-regional COMT catalytic activity (Tunbridge, 2010), possibly reflecting the influence of environmental and sex-related factors on enzymatic function (Tunbridge, 2010; Godar and Bortolato, 2014). COMT activity may also be affected by its redox status; for example, we showed that COMT activity may be robustly predicted by the activity of methionine sulfoxide reductase, which regulates the degree of oxidation of Met residues in proteins (Moskovitz, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Aberrant methyltransferase activities have been linked to significant biological consequences, and thus various regulatory strategies have evolved to properly control methyltransferases according to physiological needs5678. Well known mechanisms include phosphorylation, oxidation, automethylation, ubiquitination and other post-translational events910111213. For the majority of methyltransferases that utilize S-adenosyl-L-methionine (SAM) as the methyl group-donating cofactor, accumulation of the demethylated cofactor S-adenosyl-L-homocysteine (SAH) may lead to product inhibition; SAH hydrolases relieve the inhibitory effect by breaking down SAH into adenosine and homocysteine1415.…”
mentioning
confidence: 99%